The Barn Doors Greenstick Fracture—A New 3D Geometry for Common Osteotomies in Rhinoplasty: The First 50 Patients with 1-Year Follow-up - Ferreira, Miguel Gonçalves; Santos, Mariline (Facial Plastic Surgery, 2023)
The “barn doors greenstick fracture” is a new concept that includes three contiguous greenstick fractures: one in the central compartment of the nasal dorsum (nasal bones) and two on the lateral walls of the bony nasal pyramid. The present study aimed to describe this new concept and to report the first esthetical and functional outcomes. This prospective, interventional, and longitudinal study was performed on 50 consecutive patients undergoing primary rhinoplasty by spare roof technique B. The validated Portuguese version of the Utrecht questionnaire (UQ) for outcome assessment in esthetic rhinoplasty was utilized. Each patient answered the questionnaire online before surgery and 3 and 12 months after surgery. In addition, a visual analog scale (VAS) was used to score nasal patency for both sides. The patients also answered three questions (yes or no): (1) “Do you feel any step on your nasal dorsum?” if yes: (2) “Is that step visible?” (3) “Does it bother you?”A statistically significant improvement in UQ scores postsurgery was found, demonstrating a high satisfaction index in this patient population. Additionally, the preoperative and postoperative mean functional VAS scores showed a significant and consistent improvement on both sides (right and left). Twelve months after surgery, a step at the nasal dorsum was felt by 10% of the patients, but it was visible just in 4%, which were two females with thin skin.The barn doors greenstick concept provides a new approach to achieve a real and sustainable smooth transition in the dorsal and lateral walls. The association of the two lateral greensticks and the already described subdorsal osteotomy allows a real greenstick segment in the most critical esthetic region of the bony vault—the root of the nasal pyramid.
Keywords: rhinoplasty; spare roof technique; preservation; osteotomies